Processing of biomedical devices for tissue engineering and regenerative medicine applications - Correlo, V. M. (2016)
Tissue Engineering and Regenerative Medicine (TERM) aims at the development of biological substitutes that restore, maintain, or improve tissue function or a whole organ. In a TERM strategy, the development of a manâ made/synthetic extracellular matrix (ECM) is a critical issue, since it is need to learn how to engineer biomaterial scaffold that will help in recapitulating the early events of morphogenesis. Currently, biomaterial scaffolds are designed to support cell and tissue growth, aiming at a macroscopic level to be compatible with the mechanical loading of the surrounding organs and tissues. This chapter provides an overview on the processing techniques of natural biomaterial scaffolds for TERM approaches. The use of microparticles in the context of TERM has been highly recommended due to its high versatility. Extrusion process has been used for compounding and/or shaping biomaterials. Rapid prototyping has emerged as a powerful polymer processing technique for the production of scaffolds in the tissue engineering area.